Australian Academics and Prospective Academics Adjustment to a More Commercial Environment - Harman, Grant (OECD Publishing, 2003)
In many respects, adjustment to the new commercial environment has been painful and damaging to the academic profession in Australia. The profession is now more fragmented and has lost political influence and standing. Academic salaries have failed to keep pace with professional salaries and many academics are highly critical of changes in government higher education policy, reduced government financial support for universities and structural and management changes within their institutions. Many feel a strong sense of frustration, disillusionment and anger. However, not all adjustments have been negative. Australian academics today are better-qualified, work harder and are more productive in research than they were in the 1970s. They continue to be deeply interested in key academic roles and many still find their jobs satisfying. Many have made successful transitions to involvement in research links with industry and other entrepreneurial activities, without jeopardising their academic integrity. But the views of PhD students give cause for concern, especially dissatisfaction about course experience, uncertainty about future careers and highly negative views of both universities and academic employment...